College mathematics for business, economics, life sciences, and social sciens - Barnett, Raymond A. (Dellen Pub. Co., 1984)
This text covers mathematics of finance, linear algebra, linear programming, probability and descriptive statistics, differential and integral calculus with an emphasis on cross-discipline principles and practices. Designed to be student friendly and accessible, it develops a thorough, functional understanding of mathematical concepts in preparation for their application in other areas. Coverage concentrates on concepts and ideas, then computational skills and problem-solving.